Surgical management of massive abdominal aortic aneurysms – A case report - Mudasiru Adebayo Salami; Babatunde B Osinaike; Victor O Adegboye (Journal of Clinical Sciences, 2021)
Abdominal aortic aneurysm (AAA) is the pathologic local dilation of the abdominal aorta in which the aortic diameter is ≥ 3.0 cm. Despite reports of increased incidence worldwide, there is a paucity of reports from Nigeria. We report a case series of patients with massive abdominal aortic aneurysms (AAA) to create awareness, document unusual presentation and the peculiar challenges to management in our practice. We reviewed two consecutive patients with AAA who had open repair. Medical records of the patients were used to retrieve data including age at surgery, presenting symptoms, indication for surgery, pre-operative work up imaging, intra-operative events, post-operative complications, and follow-up up to seven 7 years postoperatively. The two patients had delayed presentations due to initial misdiagnosis. The first patient had a contained posterior rupture while the second case presented unusually with obstructive jaundice. Diagnosis and planning of surgery were aided by CT angiography and both patients had open repair with use of bifurcated Goretex grafts. Following repair, the obstructive jaundice picture resolved in the second patient. Abdominal aortic aneurysms presented late with large sizes possibly due to poor awareness of available care. Epigastric pain, pruritus and obstructive jaundice may be presenting symptoms of a large aneurysm. We recommend careful attention to the choice of operative strategy, as influenced by anatomic features of the AAA and a coherent interdisciplinary team for successful outcomes.